Asymptotic Limit to Shocks for Scalar Balance Laws Using Relative Entropy - Young-Sam Kwon (Abstract and Applied Analysis)
We consider a scalar balance law with a strict convex flux. In this paper, we study inviscid limit to shocks for scalar balance laws up to a shift function, which is based on the relative entropy.